A NEW SPECIES OF PARASCYTHOPUS DESBROCHERS FROM SYRIA (Coleoptera, Curculionidae) - Colonnelli, Enzo (Fragmenta entomologica, 2013)
Parascythopus saltinii n. sp. from Syria is described and illustrated. The new species cannot be confused with any other by its apical part of rostrum reddish and its lack of pronotal keel in combination with the elongate funicular and tarsal segments. A key to species of Parascythopus Desbrochers is included. New combination is: Parascythopus intrusus (Kôno, 1948), comb. nov. from Phyllobius to Parascythopus.